Remembering and forgetting the Scottish Highlands: Sir James Mackintosh and the forging of a British imperial identity - Gust, Onni (Cambridge University Press, 2013)
This article explores the formation of British imperial identity through a focus on the career of Sir James Mackintosh (1765–1832), a well-known Whig intellectual and imperial careerist who originally hailed from the Highlands of Scotland. Using Mackintosh's unpublished letters and autobiography, the article shows how he imagined and narrated his relationship to the Scottish Highlands from the vantage points of Bombay and London. In contrast to recent historiography that has focused on the translation of Scottish society, culture, and identity in British imperial spaces, this article argues that disidentification from the Highlands of Scotland and the erasure of different peoples, cultures, and textures of life was integral to Mackintosh's configuration of a British imperial identity.